Pharmacophore modelling and synthesis of benzaldehyde derivatives as anthelmintic agent (Ascaris lumbricoides) - Rasib, Mohd Radzi (Universiti Malaysia Sarawak (UNIMAS), 2015)
Ascariasis is an infection cause by intestinal worm called Ascaris lumbricoides. New lead compound is needed to overcome the resistance of A.lumbricoides to available drugs. Benzaldehyde is known as multiple inhibitory activities such as antimicrobial. The advancement in the computational chemistry can be utilize for designing or finding potential lead compound for anthelmintic agent. The pharmacophore modelling study on twelve benzaldehyde derivatives as a proposed compounds against protein target mitochondrial RhodoquinolFumarate Reductase from the parasite Ascaris suum with the specific inhibitor Flutolani were carried out. The target compound was obtained from Protein Data Bank (PDB) with PDB ID 3VR9. Structure-based drug design approach was applied to generate pharmacophore model, shared features generated by the interaction of proposed compounds and binding site in the active site FTN202C were analysed and the binding affinity (score) was determined. The generated shared features is a crucial parameters which are contributing toward the activity. The benzaldehyde derivatives were synthesized through Schiff base reaction and was characterized using melting point test, Fourier Transform Infra-red (FTIR), and Nuclear Magnetic Resonance (1H and 13C NMR). Biological assays of cytotoxicity using brine shrimp lethality test has been conducted and evaluation of anthelmintic activity was carried out. The pharmacophore modelling have showed that compound N'-[(E)phenylmethylidene]thiophene-2-carbohydrazide (5) was showed the highest interaction while biological assay showed that compound (5) was moderate cytotoxic and gave good result in anthelmintic evaluation activity. Thus, compound (5) was selected as the lead compound for anthelmintic agent.